A formação de professores de matemática no contexto da resolução de problemas - Justulin, Andresa Maria [UNESP] (2014)
The purpose of the present study was to investigate teachers' professional learning that arises in a study group grounded on Methodology of Mathematics Teaching-Learning-Evaluation through Problem Solving. To this end, two study groups were formed: the first one, involved seven active Mathematics teachers from a state public school, and the second one involved six future teachers from a public university in São Paulo state countryside. The research has a qualitative approach and it is grounded on Romberg's Methodological Model (1992). The instruments used in the field research were questionnaires, interviews, participant observation and the proposed problems in the study groups. Problem Solving was the focus of the discussions, particularly the Methodology of Mathematics Teaching-Learning-Evaluation through Problem Solving. Such Methodology considers the problem as the starting point for building Mathematical knowledge. It is the generator of new concepts, procedures and contents. The participants themselves, teachers and future teachers, were allowed to choose what should be developed in the fifteen meetings of each group by using, as a criterion, the most difficult contents for the students to understand during their school years, namely Algebra, Rational Numbers, Measure, Logarithms, Analytical Geometry and Trigonometry. It is important to point out that the same contents chosen by the active teachers were also considered by the Mathematics future teachers. For data analysis, four thematic axes were built: Problem Solving in learning and in the resignification of mathematical and didacticpedagogical knowledge in Mathematics teacher education; the problematization of Problem Solving in Mathematics learning and teaching practices in classrooms; the Methodology of Mathematics Teaching-learning-evaluation through Problem Solving in Mathematics teacher education; the study groups about Problem Solving as learning spaces for teachers...